This I Believe - Griffith, Ivor (Tufts Archival Research Center, 2006)
Dr. Ivor Griffith, the President and research director of the Philadelphia College of Pharmacy and Science, describes several people of different faiths which all pray to the same God and imagines them all before St. Peter at the gates of heaven then describes the accounting that will take place and why they will all be judged equally regardless of their faiths or their race.